2022
DOI: 10.3390/molecules27238127
|View full text |Cite
|
Sign up to set email alerts
|

Mebendazole Impedes the Proliferation and Migration of Pancreatic Cancer Cells through SK1 Inhibition Dependent Pathway

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has one of the highest mortality rates and requires the development of highly efficacious medications that can improve the efficiency of existing treatment methods. In particular, in PDAC, resistance to conventional chemotherapy reduces the effectiveness of anticancer drugs, decreasing the therapeutic efficiency. Sphingosine 1-phosphate (S1P), produced by sphingosine kinase (SK), plays a vital role in cancer growth, metastasis, chemotherapy, and drug resistance. Focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Another study also demonstrated that SPHK1 upregulation may play a potential role in early neoplastic transformation of inflammatory lesions in long-standing chronic pancreatitis patients [71]. Mebendazolee was proved to be used as a potential therapeutic agent for treating PDAC, because it selectively inhibited SPHK1 more than SPHK2 and regulated the levels of sphingolipids [62]. In addition, the inhibitor of SPHK1 was reported to be effective in the combination treatment of PDAC [72], and can enhance the therapeutic effect of gemcitabine [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also demonstrated that SPHK1 upregulation may play a potential role in early neoplastic transformation of inflammatory lesions in long-standing chronic pancreatitis patients [71]. Mebendazolee was proved to be used as a potential therapeutic agent for treating PDAC, because it selectively inhibited SPHK1 more than SPHK2 and regulated the levels of sphingolipids [62]. In addition, the inhibitor of SPHK1 was reported to be effective in the combination treatment of PDAC [72], and can enhance the therapeutic effect of gemcitabine [73].…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide can be converted to ceride-1-phosphate (C1P) [60] and SM [58], respectively, and is also utilized as a precursor for the generation of glycosphingolipids (GSL) including glucosylceramide and lactosylceramide [61]. Ceramide is hydroxylated by ceramidases (CDases) to yield sphingosine, which is phonologically late, by SPHK1 (also known as SK1) or SPHK2 (also known as SK2) to generate S1P [62]. In our study, we observed a slight increase in ceramide levels in TRCs, which may be related to the active metabolism of ceramide due to its role as a substrate for generation of sphingolipids with pro-survival functions.…”
Section: Discussionmentioning
confidence: 99%
“…160 MBZ has also been shown to inhibit tumor growth via the JAK2/STAT3/ Bcl-2 signaling pathway, while other studies have indicated that MBZ might modulate cancer cell migration through the S1P/FAK/ vimentin pathway. 161 MBZ has also been found to restrict the migratory and invasive tendencies of glioblastoma cells, and concurrently modulate pivotal markers in the EMT, suggesting a potential role for MBZ in mitigating glioblastoma metastasis. In oral squamous cell carcinoma, MBZ was found to downregulate specific proteins and enzymes, including FAK, Rho-A, and Rac1…”
Section: Suppressing Invasion and Metastasismentioning
confidence: 99%